UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG KDRT DALAM PERSPEKTIF PEMIKIRAN HUKUM ISLAM KLASIK DAN MODERN - Nofiardi, Nofiardi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Domestic violence known as KDRT is a common phenomenon in society. As an effort to prevent domestic violence from happening, the government passed a law aimed at preventing all forms of domestic violence. The ratification of Law Number 23 of 2004 regarding the abolition of domestic violence can be regarded as a success of women activists in Indonesia in a long-term effort to eradicate women from gender-based violence. However, in reality in the field it was found that many people thought that domestic violence was justified in Islam because of their understanding of some texts that were born to allow domestic violence such as beating a nusyuz wife. Therefore a more detailed description of how Islam's view of domestic violence is actually needed.